2018
DOI: 10.1007/s10815-018-1241-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of developmental potential of human single pronucleated zygotes derived from conventional in vitro fertilization

Abstract: This study demonstrates the usefulness of a non-invasive assessment of 1PN zygotes derived from c-IVF as an indicator of developmental potential. Furthermore, diploid 1PN zygotes do not always exhibit normal chromosome segregation at the first mitosis. A pronuclear diameter ≥ 32.2 μm just before PN breakdown might be a useful criterion to assess 1PN zygotes that are capable of further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In mice, this separation of localized chromatin modifications is conserved until the four-cell embryo stage and then gradually disappears [3]. We do not know how long separation of parental genomes continues during human preimplantation development findings consistent with segregation of genomes have been reported by Kai et al in 0PN human zygotes [2]. Dual-spindle formation in human zygotes may be extremely transient or possibly coincides with the so-called 0PN embryo.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In mice, this separation of localized chromatin modifications is conserved until the four-cell embryo stage and then gradually disappears [3]. We do not know how long separation of parental genomes continues during human preimplantation development findings consistent with segregation of genomes have been reported by Kai et al in 0PN human zygotes [2]. Dual-spindle formation in human zygotes may be extremely transient or possibly coincides with the so-called 0PN embryo.…”
mentioning
confidence: 63%
“…Given that this letter documents an isolated case of dual spindles in a human zygote, more work is needed to establish whether this is a common feature of cell cycle M-phase or a fortuitous finding that could represent abnormal processing of the maternal and paternal genomes. Moreover, it will be necessary to couple this approach with one that tracks gender-specific methylation as reported by Mio and colleagues [2]. The potential advantage of dual-spindle formation at the zygote stage of development hinges upon the fact that the spindles segregate two very different sets of chromatin: sperm DNA is highly compact; its genome relatively methylated and its transcription inert.…”
mentioning
confidence: 99%
“…This suggests that pronuclear evolution might not always reflect bi-parental diploidy and that even when PN scoring (coupled with PB scoring) is done with TLM, a subset of embryos will still be misclassified. Recent data from a study of 1PNs from conventional IVF cycles showed that 78% are diploid and could be non-invasively detected by measuring the pronuclear diameter and monitoring PN disappearance ( Kai et al , 2018 ). Although this approach is promising, live-imaging showed that the bi-parental 1PNs were prone to abnormal mitosis leading to the unequal segregation of parental genomes ( Kai et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from a study of 1PNs from conventional IVF cycles showed that 78% are diploid and could be non-invasively detected by measuring the pronuclear diameter and monitoring PN disappearance ( Kai et al , 2018 ). Although this approach is promising, live-imaging showed that the bi-parental 1PNs were prone to abnormal mitosis leading to the unequal segregation of parental genomes ( Kai et al , 2018 ). Considering the above, we therefore propose that the combined implementation of TLM with genomic technologies will provide further insights into the true genomic status of 0PNs and 1PNs and into how pronuclear evolution dynamics correlate with spindle function during mitosis and the embryonic ploidy.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of additional differences in the spindle architecture and the process of spindle assembly. For instance, the kinetics of spindle assembly in meiosis II and the first mitotic division (2 to 4 hours) is much faster than in meiosis I (12 to 16 hours) ( 2 , 12 , 13 ). Nevertheless, we do not exclude the possibility that in vitro matured oocytes, which are the main source of immature human oocytes available for research, are more prone to spindle instability during meiosis I than oocytes ovulated in vivo.…”
Section: Discussionmentioning
confidence: 99%